State Responsibility for Public Housing Ownership After the Constitutional Court Decision: Tapera - Luna, Laurenzia; Sutedja, Joshua Nathan; Frederick, Matthew; Hoek, Omar Dimitry (Dinasti Research, 2025)
The difficulty faced by low-income communities in obtaining adequate housing remains a major challenge for social policy in Indonesia. The Tapera program, intended to support housing finance, has sparked controversy as its mandatory contribution scheme has proven ineffective based on empirical data. The recent Constitutional Court decision abolishing mandatory participation has brought significant changes to the design of national housing policy. Through normative legal research employing statutory, judicial, and international comparative approaches, this study finds that the state remains constitutionally obligated to guarantee the right to housing for low-income citizens. The Tapera policy must be transformed into a more equitable, transparent, and participatory system in line with the principles of social justice and international legal standards.